Peran Kompetensi Kepribadian Guru PAI dalam Pembentukan Karakter Religius Profil Pelajar Pancasila di SMP Karang Arum Kecamatan Cilengkarang Kabupaten Bandung - Nia Ardianingsih; Kun Nurachadijat; Yurna Yurna; Aeni Latifah; Siti Qomariah; Dadang Sahroni; Mulyawan Safwandy N; Sri Widaningsih (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
The teacher has a strategic position at the forefront of efforts to build the nation, in this case the field of education, as their performance in all educational activities is determined by how well they perform at the institutional, instructional, and experimental levels. This study aims to investigate the extent to which the personality competence of PAI teachers at Karang Arum Middle School in Cilengkrang District, Bandung Regency, play a role in the development of the religious character of their students' profiles. The results of this research show a substantial positive association between the dependent variable in this study, the formation of the students' religious character, and the teacher's personality competence as an independent variable. With it, Personality Competence significantly aids in the development of its students' religious character. In conclusion, for those in charge of making decisions, it is unquestionably necessary to develop the personality skills of the teachers if you want to raise the caliber of students' religious character.